Ultimate Strength of Fixed Offshore Platforms Subjected to Near-Fault Earthquake Ground Vibration - Hesam Sharifian; Khosro Bargi; Mohamad Zarrin (Shock and Vibration)
The pile foundation nonlinearity and its influence on the ultimate capacity of fixed platforms have not comprehensively been covered by previous researchers. In this study, the seismic behavior and capacity of a newly designed and installed Jacket Type Offshore Platform (JTOP) located in the Persian Gulf is investigated by conducting Incremental Dynamic Analysis (IDA) using a suit of near-fault ground motions. Additionally, two modified models of the original platform are created by slightly increasing the diameter of the pile foundation and also softening the jacket part for evaluating the importance of the pile foundation and seismic soil-pile structure interaction on the dynamic characteristics of the JTOPs. Valuable discussions are provided to explore various aspects of the dynamic behavior of JTOPs by presenting individual and multirecords IDA curves using effective Engineering Demand Parameters (EDPs). Comparing the results of the three platform collapse fragility curves, it is concluded that the pile foundation plays a very important role in the dynamic response of offshore platforms and can drastically alter the ultimate strength of the platform together with its collapse capacity. It is observed that the proportional distribution of nonlinear behavior in the pile foundation and jacket part is the key factor in the enhancement of the ultimate strength of JTOPs. On the basis of the results derived from this paper, it is recommended that some basic requirements should be developed in order to ensure that the coupling ductility of pile foundation and jacket part is optimized during the design process. Furthermore, according to the findings from this study, some practice recommendations are presented to be devised within the design step.